The tones of numerals and numeral-plus-classifier phrases: on structural similarities between Naxi, Na and Laze - Michaud, Alexis (2024)
Numeral-plus-classifier phrases have relatively complex tone patterns in Naxi, Na (a.k.a. Mosuo) and Laze (a.k.a. Shuitian). These tone patterns have structural similarities across the three languages. Among the numerals from ‘1’ to ‘10’, three pairs emerge: ‘1’ and ‘2’ always have the same tonal behaviour; likewise, ‘4’ and ‘5’ share the same tone patterns, as do ‘6’ and ‘8’. Even those tone patterns that are irregular in view of the synchronic phonology of the languages at issue are no exception to the structural identity within these three pairs of numerals. These pairs also behave identically in numerals from ‘11’ to ‘99’ and above, e.g. ‘16’ and ‘18’ share the same tone pattern. In view of the paucity of irregular morphology—and indeed of morphological alternations in general—in these languages, these structural properties appear interesting for phylogenetic research. The identical behaviour of these pairs of numerals originates in morpho phonological properties that they shared at least as early as the stage preceding the separation of Naxi, Na and Laze, referred to as the Proto-Naish stage. Although no reconstruction can be proposed as yet for these shared properties, it is argued that they provide a hint concerning the phylogenetic closeness of the three languages.